Topophilia and Chronophobia - Rappaport, Alexander (project baikal, 2014)
In the article architectural ideas of space and time are connected with radical changes in the world views, historical and perpetual, transcendental and radical. It is a paradoxical comeback of Christian Renaissance culture to pagan Roman and Greek antiquity from its recent achievements denied in gothic architecture. Avant-garde in 20th century did even more radical attempt to tie prehistoric past and futuristic utopia in radical architectural forms. Today we approach a new revolutionary change of space and time concepts coming to the end of modernism and global disillusions of cosmic expansion.